The Utilization of Colonial Historical Sites in the City of Palembang as a Learning Resource Based on Outdoor Learning - Riki Andi Saputro (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2021)
The activeness of all students’ senses can occur if students participate actively in learning activities. One of the learning activities that are able to actively involve students is by the way of outdoor learning. Research sub-focus: Cultural Heritage and Colonial Historical Sites. The formulation of the problem in this study: Historical value in the colonial period sites in the city of Palembang. The purpose of this research is to provide resource that can be used in learning History in High School. The benefit of this research is the availability of source and references for writing the history of the colonial period in Palembang. This research used history (historical) method, assisted by scientific approach from various fields (multi-approach) such as theological, political, anthropological and sociological sciences. The results of the research on colonial historical sites in the city of Palembang contain as a source of learning based on outdoor learning in high school.